IMPLEMENTASI KEBIJAKAN PERMENDAGRI NO. 14 TAHUN 2019 TENTANG PENERIMAAN PAJAK KENDARAAN BERMOTOR PADA BADAN PENDAPATAN DAERAH PROVINSI LAMPUNG. - Sukismanto Aji; Achmad Suharyo; Zeldawaty Zeldawaty (Universitas Bandar Lampung (UBL), 2020)
The problems in this study are: (1) How to implement Permendagri No. policy. 14 of 2019 motor vehicle tax revenue at the Lampung Provincial Opinion Board. (2) What aspects hinder the implementation of Permendagri No. policy. 14 of 2019 motor vehicle tax receipts at the Lampung Provincial Opinion Board.The research method used in this research is to use qualitative research types with descriptive analysis methods. The use of this method is to study and describe qualitatively how Permendagri No. policy is implemented. 14 of 2019 motor vehicle tax revenue at the Lampung Provincial Opinion Board.The results showed that the implementation of Permendagri No. policy. 14 of 2019 motor vehicle tax revenue, shows that the policy has been implemented but not yet optimal, from (1) The idealized policy, (ideal policy), good, but the implementation is not fully implemented, (2) The target group (policy targets ), it is appropriate that only those taxpayers who have not complied, (3) The implementing organization, (implementing organization), has been carried out by the Regional Revenue Agency of Lampung Province, but has not met the target set, (4) The environmental factors (Environmental factors ), is conducive and the spirit of cooperation both within organizations and between related agencies. Inhibiting aspects, that is, sometimes employees in charge of motor vehicle tax receipts at the Lampung Province Regional Revenue Agency, are less responsive, and there are still frequent bureaucratic sebara services, which seem complicated. on the side of the taxpayer not yet fully aroused the awareness to pay the tax on the vehicle whose payment is due, so the target set by the Lampung Province Regional Revenue Agency in implementing Permendagri No. policy. 14 of 2019 has not been realized as specified.